Metabolomics for biomarker discovery in schistosomiasis: A systematic scoping review - Herald Midzi; Arthur Vengesai; Victor Muleya; Maritha Kasambala; Tariro Lavender Mduluza-Jokonya; Isaac Chipako; Clayton Edmore Siamayuwa; Francisca Mutapi; Thajasvarie Naicker; Takafira Mduluza (Frontiers Media, 2023)
Background: Metabolomic based approaches are essential tools in the discovery of unique biomarkers for infectious diseases via high-throughput global assessment of metabolites and metabolite pathway dysregulation. This in-turn allows the development of diagnostic tools and provision of therapeutics. In this review, we aimed to give an overview of metabolite biomarkers and metabolic pathway alterations during Schistosoma haematobium and Schistosoma mansoni infections.